Classification and characteristics of ammonia combustion in well stirred reactor - Liu, Xiangtao; Wang, Guochang; Wang, Feifei; Li, Pengfei; Si, Jicang; Hanif, Farhan; Mi, Jianchun (International journal of hydrogen energy, 2024)
The present work investigates the regime classification and chemical characteristics of the premixed ammonia combustion in a well stirred reactor (WSR). Three combustion regimes can be classified based on the lowest autoignition and highest extinction temperatures and the reacting temperature increment, which are: (i) flameless combustion (FLC); (ii) high temperature combustion (HTC); (iii) traditional combustion (TC). When introducing the upper limit of NOx emission into the classification, MILD combustion can be defined as a sub-regime of FLC. Relative to the methane counterpart, the ammonia combustion is found to exhibit larger FLC and smaller HTC regimes delimited by the inlet temperature and oxygen fraction. It is also revealed that the MILD combustion of ammonia differs significantly from its burning under other regimes in heat production and NO formation mechanisms. In the MILD combustion, multiple reactions dominate the heat production while the DeNOx route greatly reduces the NO formation. Contrarily, in other combustion regimes, heat is controlled by one or two specific reactions while notably the Extended Zeldovich route dominates the NO destruction. Moreover, the working temperature controls the top reactions for both heat and NOx productions, regardless of different combustion regimes. •Regime classification, heat release and NO formation of NH3 oxidation are studied.•The NOx emission criterion is introduced into the definition of MILD combustion.•The NH3 combustion shows a larger flameless region against burning CH4.•The working temperature controls top reactions for both heat and NOx productions.•The leading NO reduction reactions are distinct in MILD and other regimes.